Digging the Talmud in Ancient Meiron - Meyers, Eric M. (The Biblical archaeology review, 1978)
The Talmud is, after the Bible itself, Judaism’s most significant and revered collection of sacred writings. Although the Talmud was in fact written and compiled between the Second and Fifth centuries A.D., rabbinic tradition holds that it was given to Moses at Mount Sinai together with the Torah. The Torah is referred to as […]